Solubility and dissolution enhancement of HPMC ‑ based solid dispersions of carbamazepine by hot‑melt extrusion technique - Javeer, Sharadchandra Dagadu; Amin, Purnima Dhanraj (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this study was to investigate solid dispersions (SDs) of poorly water soluble drug carbamazepine (CBZ), prepared using low viscosity grade hydroxypropyl methyl cellulose (HPMC) (Methocel® E3 LV and Methocel® E5 LV) by hot‑melt extrusion (HME) technology. Saturation solubility and dissolution profile of CBZ was studied. Characterization of hot‑melt extruded samples was done by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X‑ray diffraction studies (XRD). The result of the study showed the conversion of crystalline form of drug into amorphous form indicating increase in saturation solubility and dissolution rate of CBZ. Key words: Carbamazepine, hot‑melt extrusion, hydroxypropyl methyl cellulose